Identification and stratification of systemic lupus erythematosus patients into two transcriptionally distinct clusters based on IFN-I signature. (April 2021) - Shobha, Vineeta; Mohan, Anu; Malini, AV; Chopra, Puneet; Karunanithi, Preethi; Subramani Thulasingam, Siva; Selvam, Sabariya; Deyati, Avisek; Srivastava, Ratika; Basavanthappa, Sushma; Lemos, Nadine; Sunitha, S Margaret; et al.
Objective: Despite the significant advancement in the understanding of the pathophysiology of systemic lupus erythematosus (SLE) variable clinical response to newer therapies remain a major concern, especially for patients with lupus nephritis and neuropsychiatric systemic lupus erythematosus (NPSLE). We performed this study with an objective to comprehensively characterize Indian SLE patients with renal and neuropsychiatric manifestation with respect to their gene signature, cytokine profile and immune cell phenotypes. Methods: We characterized 68 Indian SLE subjects with diverse clinical profiles and disease activity and tried to identify differentially expressed genes and enriched pathways. To understand the temporal profile, same patients were followed at 6 and 12-months intervals. Additionally, auto-antibody profile, levels of various chemokines, cytokines and the proportion of different immune cells and their activation status were captured in these subjects. Results: Multiple IFN-related pathways were enriched with significant increase in IFN-I gene signature in SLE patients as compared to normal healthy volunteers (NHV). We identified two transcriptionally distinct clusters within the same cohort of SLE patients with differential immune cell activation status, auto-antibody as well as plasma chemokines and cytokines profile. Conclusions: Identification of two distinct clusters of patients based on IFN-I signature provided new insights into the heterogeneity of underlying disease pathogenesis of Indian SLE cohort. Importantly, patient within those clusters retain their distinct expression dynamics of IFN-I signature over the time course of one year despite change in disease activity. This study will guide clinicians and researchers while designing future clinical trials on Indian SLE cohort.